Formulation and evaluation of atorvastatin calcium trihydrate Form I tablets - Karen Andrea Salazar-Barrantes; Ariadna Abdala-Saiz; José Roberto Vega-Baudrit; Mirtha Navarro-Hoyos; Andrea Mariela Araya-Sibaja (PLoS ONE, 2025)
Solid forms transformations and new crystal structures of an active pharmaceutical ingredient (API) can occur due to various manufacturing process conditions, especially if the drug substance is formulated as a hydrate. The conversion between hydrate and anhydrate forms caused by changes in temperature and humidity must be evaluated because of the risk of dehydration and phase transitions during the manufacturing process. Differences in physicochemical, mechanical, and rheological properties have been observed between solid forms of the same API that can cause manufacturing and product-related issues. Atorvastatin calcium trihydrate (ACT) is a synthetic lipid-lowering agent that was discovered during Lipitor® (its anhydrous form) Phase 3 clinical trials after passing Phase I and II. This case highlights the importance of routinely performing solid form screenings because of the probability of finding new solid forms during the development and scale-up process. Therefore, in this contribution, ACT tablet formulation was performed and evaluated starting from the compatibility of 1:1 proportions of drug and the excipients microcrystalline cellulose 101 (MCC 101), calcium carbonate, lactose monohydrate, croscarmellose sodium, hydroxypropyl cellulose, magnesium stearate, and polysorbate 80. Then, 40 mg ACT tablets were prepared on a small pilot scale, and manufacturing process assessment was conducted by sampling process stages selected as critically prone to solid forms formation or phase transition. Final product quality was evaluated regarding weight variation, hardness, disintegration, dissolution, and assay tests. Powder X-ray diffraction (PXRD), Fourier transform infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) were applied to solid state evaluation. The starting raw material was confirmed to be ACT Form I. From the preformulation studies, PXRD, FT-IR and TGA analyses showed no interactions between ACT and excipients, while DSC results revealed a physical interaction with MCC 101, not considered an incompatibility. The effect of the tablet manufacturing process was achieved by amorphization, while some ACT long-range crystalline structure remained, as confirmed by PXRD, FT-IR and DSC. However, the tablets’ quality parameters were found to be within the acceptable range of both the pharmacopeia guidelines and manufacturer parameters regarding weight variation, hardness, disintegration, dissolution, and assay tests.